FAKTOR-FAKTOR YANG MEMPENGARUHI DARI SISTEM PEMASARAN DIGITAL PADA SEBUAH PERUSAHAAN DALAM PENJUALAN - Ageng Saepudin Kanda S; N. Hilmi Kurotul Aeni (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The rapid development of information technology currently has an impact on society in supporting various business activities, both large and small, so that they can be recognized globally. The most obvious impact is that apart from being known, it can also increase sales volume and profits. Digital Marketing is a marketing medium that has a huge influence. By using digital marketing, in this case social media, Tirtamulya Cafe markets a place to hang out and gather with family. The cafe started from many swimming pool visitors who wanted to eat and gather with their families but the space was inadequate, so now the Tirtamulya Cafe is being built with a comfortable place for family gatherings. Previously, the cafe was not well known, but after learning about the existence of social media, the Tirtamulya team started promoting the cafe on social media. and after becoming famous on social media, sales volume increased rapidly compared to when selling using the old method. Digital marketing is seen as the best media as the most effective and efficient means of promotion and is able to increase sales volume significantly, from monthly incom.